Psychometric properties of Hindi version of child oral impact on daily performances (C-OIDP) index amongst school children in North India - Preeti Dhawan; Aditi Singh; Anubha Agarwal; Himanshu Aeran (Journal of Oral Biology and Craniofacial Research)
Aim: To assess validity and reliability of Hindi version of Child Oral impact on daily performances (C-OIDP) index among school children in North India. Material and methodology: Descriptive cross sectional study was conducted amongst 250, 11–12 year old school children in primary schools of Rishikesh, Uttarakhand, India. The study was done in two phases: first phase included assessment of Psychometric and linguistic properties of hindi version of C-OIDP index which was then pilot tested on study subjects. Phase two comprised of the actual main study which included the re-assessment of Hindi C-OIDP index on the entire study population. The pilot study comprised of 40 school children while the main study was conducted on 250 school children. Results: The inter-item correlation coefficient ranged from 0.1 to 0.786 while corrected item total correlation coefficient ranged from 0.176 (smiling) to 0.843 ((cleaning). The standardised Cronbach's Alpha coefficient was 0.88. Moreover, the alpha coefficients didn't increase upon deleting any of the items. Weighted kappa was 0.85 & ICC was 0.9. Children with higher scores were less satisfied with their mouth (p- 0.001) in case of concurrent validity. Conclusion: Hindi Child Oral Impact on Daily Performances index can be used as a valid and reliable instrument in measuring OHRQoL. of Paediatric North Indian population.